Analysis of Factors Influencing Stigma Against Mental Disorders in Indonesia: Systematic Literature Review - Davies, Jocelyn (HM Publisher, 2024)
Introduction: Stigma towards mental disorders is an important public health problem in Indonesia. This stigma can have a negative impact on the lives of people with mental disorders (ODGM), such as discrimination, social isolation, and an increased risk of suicide. This research aims to analyze the factors that influence the stigma of mental disorders in Indonesia. Methods: This research uses a systematic literature review method. Research data was obtained from electronic literature searches on PubMed, Medline, and Google Scholar. Research inclusion criteria were research published in reputable scientific journals, published in the 2010-2022 period, and discussing factors that influence the stigma of mental disorders in Indonesia. Results: The research results show that there are five factors that influence the stigma of mental disorders in Indonesia, namely: low knowledge about mental disorders, negative views about mental disorders, negative experiences with people with mental disorders, cultural factors, and socioeconomic factors. Conclusion: Negative views about mental disorders can come from various sources, including family, friends, society, and mass media. Education about mental disorders needs to be improved to increase public knowledge about mental disorders.